2015
DOI: 10.1007/s00253-015-6527-z
|View full text |Cite
|
Sign up to set email alerts
|

An efficient high-throughput screening assay for rapid directed evolution of halohydrin dehalogenase for preparation of β-substituted alcohols

Abstract: Halohydrin dehalogenases (HHDHs) are an important class of enzymes for preparing optically active haloalcohols, epoxides, and β-substituted alcohols. However, natural HHDHs rarely meet the requirements of industrial applications. Here, a novel high-throughput screening (HTS) methodology for directed evolution of HHDH was developed based on the colorimetric determination of azide. In this method, azide was involved in the HHDH-catalyzed ring-opening process and the decrease of azide was used to quantitatively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“… [1] Natively, HHDHs perform the dehalogenation of β ‐haloalcohols via formation of the corresponding epoxide. [2] Their ability to also catalyze the reverse reaction (i. e. epoxide ring opening) with anionic C‐, N‐, O‐, S‐ and halide nucleophiles [3] provides divergent access to an impressive repertoire of valuable products[ 4 , 5 , 6 , 7 , 8 , 9 ] (Scheme 1 ). This catalytic promiscuity, combined with the diversity of sequences available from databases, has made HHDHs attractive biocatalysts for kinetic resolutions and desymmetrization reactions.…”
Section: Introductionmentioning
confidence: 99%
“… [1] Natively, HHDHs perform the dehalogenation of β ‐haloalcohols via formation of the corresponding epoxide. [2] Their ability to also catalyze the reverse reaction (i. e. epoxide ring opening) with anionic C‐, N‐, O‐, S‐ and halide nucleophiles [3] provides divergent access to an impressive repertoire of valuable products[ 4 , 5 , 6 , 7 , 8 , 9 ] (Scheme 1 ). This catalytic promiscuity, combined with the diversity of sequences available from databases, has made HHDHs attractive biocatalysts for kinetic resolutions and desymmetrization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the adrenaline assay for HHDHs is rather restricted in terms of epoxide substrates and nucleophiles that can be applied. The other HHDH assay reported for epoxide ring opening reactions was specifically developed for using azide as nucleophile (Wan et al 2015a ). The assay is based on the quantification of unreacted azide by adding FeCl 3 solution, which results in formation of a blood red Fe(III)/azide complex specifically absorbing at 460 nm — an assay principle already reported in 1932 (Labruto and Randisi 1932 ).…”
Section: Assay Developmentsmentioning
confidence: 99%
“…The assay is based on the quantification of unreacted azide by adding FeCl 3 solution, which results in formation of a blood red Fe(III)/azide complex specifically absorbing at 460 nm — an assay principle already reported in 1932 (Labruto and Randisi 1932 ). Now, Wan et al ( 2015a ) adapted and optimized this assay for the screening of a random mutagenesis library in order to identify mutants of HheA3 from P. lavamentivorans with improved activity in the conversion of ethyl 4-chloro-3-hydroxybutyrate into ethyl 4-azido-3-hydroxybutyrate.
Fig.
…”
Section: Assay Developmentsmentioning
confidence: 99%
“…Its crystal structure and catalytic mechanism have been determined [14]. In the previous report, it is indicated that HheC and its mutants were efficient biocatalysts for the enantioselective formation of optically pure epoxides, halohydrins and chiral β-substituted alcohols from racemic halohydrins and epoxides [15,16], but the production ECH from prochiral 1,3-DCP using HheC was racemic [17,18].…”
Section: Introductionmentioning
confidence: 97%